2021
DOI: 10.1097/cxa.0000000000000124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cannabis Use on Psychotic and Mood Symptoms: A Systematic Review

Abstract: Background: The association between cannabis use and psychiatric disorders has been extensively investigated, but the effect of cannabis use on the induction and persistence of psychiatric symptoms in healthy individuals is less clear. We determines whether cannabis contributes to the induction and persistence of psychotic, depressive, or (hypo)manic symptoms in healthy individuals. We identified populations that are most susceptible to these effects, in addition to cannabis use behaviors that incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 109 publications
1
11
0
Order By: Relevance
“…This systematic review and meta-analysis found a dose–response relationship between the frequency of cannabis use and the development of psychosis, as shown by previous reviews (Hasan et al, 2020 ; Kiburi et al, 2021 ; Marconi et al, 2016 ; Moore et al, 2007 ; Polkosnik et al, 2021 ; van der Steur et al, 2020 ). Prior meta-analyses specifically documented a higher risk among daily users, mostly as compared to no or lower frequency use, with ORs ranging from 2.09 to 3.90 (Kiburi et al, 2021 ; Marconi et al, 2016 ; Moore et al, 2007 ).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…This systematic review and meta-analysis found a dose–response relationship between the frequency of cannabis use and the development of psychosis, as shown by previous reviews (Hasan et al, 2020 ; Kiburi et al, 2021 ; Marconi et al, 2016 ; Moore et al, 2007 ; Polkosnik et al, 2021 ; van der Steur et al, 2020 ). Prior meta-analyses specifically documented a higher risk among daily users, mostly as compared to no or lower frequency use, with ORs ranging from 2.09 to 3.90 (Kiburi et al, 2021 ; Marconi et al, 2016 ; Moore et al, 2007 ).…”
Section: Discussionsupporting
confidence: 82%
“…Recent research has confirmed the importance of genetic influences, specifically polymorphisms on specific genes (e.g. COMT, AKT1) that make affected individuals more vulnerable to the psychogenetic effects of cannabis (Misiak et al, 2018 ; Polkosnik et al, 2021 ; van der Steur et al, 2020 ). The present review further compounds the evidence that specific (frequent) cannabis exposure patterns appear to significantly contribute to the multifactorial interplay toward psychosis outcomes.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations